2021
DOI: 10.1080/22221751.2021.1882884
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk analysis of mobile colistin resistance and extended-spectrum β-lactamase genes carriage in pet dogs and their owners: a population based cross-sectional study

Abstract: Prevalence and risk analysis of mobile colistin resistance and extended-spectrum βlactamase genes carriage in pet dogs and their owners: a population based cross-sectional study, Emerging Microbes & Infections,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 35 publications
2
24
2
Order By: Relevance
“…The close contact between companion animals and humans enhances the risk of bacterial and even antimicrobial-resistant bacterial transmission across animals or humans by horizontal transfer and clonal spread [ 11 ]. Previous studies have shown that antimicrobial-resistant E. coli are frequently isolated from dogs and cats [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The close contact between companion animals and humans enhances the risk of bacterial and even antimicrobial-resistant bacterial transmission across animals or humans by horizontal transfer and clonal spread [ 11 ]. Previous studies have shown that antimicrobial-resistant E. coli are frequently isolated from dogs and cats [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…mcr genes were detected in E. coli and Pseudomonas aeruginosa [ 41 ]. However, dogs and their owners have high potential colonization of antibiotic-resistant bacteria [ 42 ]. Colistin-resistance genes have also recently been detected in dogs in South Korea [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zoonotic transmission from pets to their owners has already been reported in several studies. It is important to establish strict hygiene conditions and diverse approaches to reduce zoonotic transmission of mcr -producing bacteria [ 42 , 47 , 48 ]. Bacteria that carry mcr genes can cause diseases such as urinary tract infections, previously reported to be linked to the presence of E. coli carrying the mcr-1 gene [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in the case of companion animals, such as dogs and cats, not only veterinarians but also animal owners are at risk of acquiring multiresistant zoonotic bacterial pathogens. Previous studies have shown that there are numerous examples of dog and cat owners sharing (multi)resistant bacteria with their pets [ 8 , 9 , 10 , 11 ]. Enterococci, in particular Enterococcus faecalis and Enterococcus faecium , but also the Gram-negative species Escherichia coli , Pseudomonas aeruginosa , and Acinetobacter baumannii have zoonotic potential.…”
Section: Introductionmentioning
confidence: 99%